Multi-Level DC-DC Converter for High Gain Applications - Girish Ganesan R; M. Prabhakar (Institute of Advanced Engineering and Science, 2013)
The output voltage from most renewable energy sources like photovoltaic arrays and fuel cells will be at low level. This must be stepped up considerably for practical utilization or grid connection. The presented multilevel boost converter DC-DC converter topology consists of the conventional boost converter and voltage doubler stages to provide high voltage gain. The proposed topology uses only one switch along with one inductor, (2N-1) diodes and (2N-1) capacitors for obtaining an output which is N times the conventional boost converter. In this topology, each device blocks only one voltage level. The main advantages of this topology are continuous input current, large gain without high duty cycle or transformer, modularity and use of devices with low voltage ratings. Experimental results obtained from the 100W prototype demonstrate the voltage gain capability of the converter and validates the converter design.DOI: http://dx.doi.org/10.11591/ijpeds.v4I1.4870